Post Tonsillectomy Nausea and Vomiting: Role of Single Intravenous Dose of Dexamethasone - Muhammad Ismail Khan; Mohammad AminJan Mahsud; Muhammad Marwat; Waliullah Khan (Gomal Journal of Medical Sciences, 2013)
Background: Tonsillectomy is the commonest ENT surgical procedure. The common postoperative morbidities associated with tonsillectomy are nausea, vomiting, pain and bleeding. The objective of this study was to compare the effects of single intra-operative intravenous dose of dexamethasone versus control group on frequency of post tonsillectomy nausea and vomiting and need for rescue anti-emetics in the first 24 hours. Material and Methods: This comparative study was conducted at Department of ENT, DHQ Hospital, Lakki Marwat from January 2009 to June 2010. Patients of both gender aged 6-30 years were listed for elective tonsillectomy or adenotonsillectomy. Patients with history of acute tonsillitis within six weeks, bleeding diathesis, or those with a known contraindication to steroids, were excluded. Patients were divided into group 1 (treatment) and 2 (control) of 50 each on alternate basis. A single dose of dexamethasone was given to patients of group 1 intra-operatively, whereas patients in group 2 received nothing. The difference in frequency of postoperative nausea, vomiting and need for rescue anti-emetics between the two groups was analyzed by Chi-Square test. Results: Out of 100 patients, 66 were male and 34 female. Statistically significant decrease in frequency of nausea, vomiting and need for rescue anti-emetics (p=values 0.006, 0.014 and 0.008 respectively) was noted in patients treated with dexamethasone. Conclusion: Single dose of dexamethasone given intra-operatively reduces the frequency of post-operative nausea, vomiting and the need for rescue anti-emetics in the first 24 hours.